2012
DOI: 10.3945/ajcn.111.023812
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative data on the magnitude of the systemic inflammatory response and its effect on micronutrient status based on plasma measurements

Abstract: The clinical interpretation of plasma micronutrients can be made only with knowledge of the degree of inflammatory response. A reliable clinical interpretation can be made only if the C-reactive protein is <20 mg/L (plasma zinc), <10 mg/L (plasma selenium and vitamins A and D), or <5 mg/L (vitamins B-6 and C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
194
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(215 citation statements)
references
References 32 publications
6
194
1
3
Order By: Relevance
“…Firstly, the serum levels of trace elements in patients were tested after the diagnosis of breast cancer, but before therapy. Injuries and infections were reported to alter concentrations of a variety of micronutrients (Duncan et al 2012). Nevertheless, our findings still offer a direction to future prospective researches in China as well as in other regions and countries.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, the serum levels of trace elements in patients were tested after the diagnosis of breast cancer, but before therapy. Injuries and infections were reported to alter concentrations of a variety of micronutrients (Duncan et al 2012). Nevertheless, our findings still offer a direction to future prospective researches in China as well as in other regions and countries.…”
Section: Discussionmentioning
confidence: 98%
“…They postulated that these findings could be attributed to redistribution, overhydration and increased requirements for antioxidants. More recently Duncan and coworkers (2012) reported that in a large cohort of patients, there was a larger fall of 78% in plasma AA for CRP concentrations of >80 mg/l [4].…”
Section: Introductionmentioning
confidence: 98%
“…6 Indeed, recent studies have quantified the impact of the systemic inflammatory response, as evidenced by both serum C-reactive protein (CRP) and albumin, on serum vitamins and micronutrients. [7][8] With reference to iron status, hepcidin is a key regulator of iron homeostasis, acting to reduce iron export and cause sequestration of iron through the inhibition of ferroportin.…”
Section: Introductionmentioning
confidence: 99%